Fortress Europe as Empire and Ireland's National Diaspora Centre. Issue 3 (3rd July 2017) - Boucher, Gerard; Watson, Iarfhlaith
Abstract : This article develops a concept of core–periphery schema to investigate how the underlying cultural structures of social groups and insider–outsider relations are represented visually. We apply both the concept of core–periphery schemas as well as the concept of smaller states to case studies of existing diagrammatic visual representations in academic and policy publications. The specific cases we examine are Geddes' (2000) and Gravier's (2015) construction of Fortress Europe and Europe as Empire, as well as Fáilte Ireland's (2013) construction of a schema to support the building of a National Diaspora Centre in Ireland. Linking the concepts of core–periphery and smaller states, the vulnerabilities and perceptions of threats, and responses to these by states and regional polities like the European Union are present in the visual schema. The results largely support the argument that there exists a widely shared cultural structure in a core–periphery schema, which is transmittable across social contexts and time periods, and is flexible in terms of how different actors can construct it visually to suit individual, situational and contextual factors.